Increasing Consumer Buying Intention through Strengthening Promotion, Brand and Market Analysis - Oktiansyah, Sella; Nuvriasari, Audita (PT FORMOSA CENDEKIA GLOBAL, 2024)
This community service program at PT Sebangku Kuliner aims to increase consumer buying interest in Taiyaki Minnasan and Ladybee Taiyaki Jogja through strengthening promotions, brands, and market analysis. Then, content planning is made so that business social media is more organized and directed. The method used is through the transfer of knowledge and technology which is realized in the creation of content planning so that business social media is more focused, making attractive promotional designs, and market analysis which plays an important role in knowing the target market. The results of the work program carried out successfully identified the target market, increased Instagram performance by 70%, targeted branding, and succeeded in adding new marketing channels through the Tiktok platform.